Status Of Endemic Plants Of Bangladesh And Conservation Management Strategies - Rahman, M Atiqur; Rashid, M Enamur (International Journal of Environment, 2013)
The present study was aimed at recognizing the status of 28 endemic plants of Bangladesh and determining their conservation management strategies. These endemics belong to 17 angiosperm families and constitute about 0.78% of the total species of the country. Of these endemics, 2 species were least concern, 10 rare and 7 endangered, and need to give immediate conservation priority. Another 9 endemics were assessed to be extinct since no report of collection for more than 100 years was available and could not be traced in the wild. An enumeration of these endemics is presented, each cited with updated nomenclature, bangla names, type, habit, ecology, potential values, places and status of occurrence, threats to the species, conservation status for sustainable management strategies. List of examined specimens of these endemics, wherever available, is also provided. Photographs of 24 endemics are also presented. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 231-249 DOI: http://dx.doi.org/10.3126/ije.v2i1.9224